Mesoionic Imines (MIIs): Strong Donors and Versatile Ligands for Transition Metals and Main Group Substrates - Rudolf, Richard (2022)
We report the synthesis and the reactivity of 1,2,3-triazolin-5-imine type mesoionic imines (MIIs). The MIIs are accessible by a base-mediated cycloaddition between a substituted acetonitrile and an aromatic azide, methylation by established routes and subsequent deprotonation. C=O-stretching frequencies in MII−CO2 and −Rh(CO)2Cl complexes were used to determine the overall donor strength. The MIIs are stronger donors than the N-heterocyclic imines (NHIs). MIIs are excellent ligands for main group elements and transition metals in which they display substituent-induced fluorine-specific interactions and undergo C−H activation. DFT calculations gave insights into the frontier orbitals of the MIIs. The calculations predict a relatively small HOMO–LUMO gap compared to other related ligands. MIIs are potentially able to act as both π-donor and π-acceptor ligands. This report highlights the potential of MIIs to display exciting properties with a huge potential for future development.